Revisiting the therapeutic potential of tocotrienol. (20th June 2022) - Ranasinghe, Ranmali; Mathai, Michael; Zulli, Anthony
Abstract: The therapeutic potential of the tocotrienol group stems from its nutraceutical properties as a dietary supplement. It is largely considered to be safe when consumed at low doses for attenuating pathophysiology as shown by animal models, in vitro assays, and ongoing human trials. Medical researchers and the allied sciences have experimented with tocotrienols for many decades, but its therapeutic potential was limited to adjuvant or concurrent treatment regimens. Recent studies have focused on targeted drug delivery by enhancing the bioavailability through carriers, self‐sustained emulsions, nanoparticles, and ethosomes. Epigenetic modulation and computer remodeling are other means that will help increase chemosensitivity. This review will focus on the systemic intracellular anti‐cancer, antioxidant, and anti‐inflammatory mechanisms that are stimulated and/or regulated by tocotrienols while highlighting its potent therapeutic properties in a diverse group of clinical diseases.